Large‐Scale Traveling Ionospheric Disturbances Over the European Sector During the Geomagnetic Storm on March 23–24, 2023: Energy Deposition in the Source Regions and the Propagation Characteristics - Nykiel, Grzegorz; Ferreira, Arthur Amaral; Günzkofer, Florian Ludwig; Iochem, Pelin; Tasnim, Samira; Sato, Hiroatsu (Journal of Geophysical Research: Space Physics, 2024)
Multiple Large-Scale Traveling Ionospheric Disturbances (LSTIDs) are observed in the European sector in both day-time and night-time during the magnetic storm on March 23–24, 2023. The Total Electron Content (TEC) observation from a network of GNSS receivers shows the propagation of LSTIDs with amplitudes between around 0.5 and 1 TECU originating from auroral and polar cusp regions down to southern Europe (35°N) with velocities between around 500 and 1,600 [m/s]. We study the energy deposition to the LSTIDs in the source regions and the resulting horizontal propagation over storm-time background density by using continuous measurements of EISCAT incoherent scatter radars in northern Norway and Svalbard that allow for estimating the source energy to the thermosphere-ionosphere system via Joule heating and particle precipitation. Both EISCAT and GNSS TEC data show that the electron density decreased to 50% in the auroral zone after the storm onset. The ionospheric heating caused a nearly 250% increase in the electron temperature above 200 km altitude and the ion temperature above 100 km altitude. We find that Joule Heating acts as a primary energy source for the night-time LSTIDs triggered in the auroral region, while the day-time LSTIDs can be also driven by precipitating particles in the polar cusp. We also find that a significant background density decrease over the whole European sector is caused by this storm for the following day, during which almost no clear LSTIDs are observed.